A Spline-based Flexible Method of Virtual Force Design for Dynamic Motion Planning of Robots. Issue 3 (3rd May 2016) - Choi, S.H.; Zhu, W.K.
ABSTRACT: Virtual force approach is preferable for motion planning of mobile robots in dynamic environments. It composes virtual attractive forces to drive robots to destinations and virtual repulsive forces to steer robots away from neighbouring robots. However, most traditional methods use functions with limited controllable parameters, compromising design flexibility essential for smooth yet responsive robot motions. This paper proposes a spline-based method to enhance design flexibility of virtual forces that streamline robot motions. We take advantage of local controllability of interpolating cubic splines to generate desirable smooth virtual forces for robots. This merit facilitates responsive robot motions in dynamic situations. A case study of autonomous military robots is presented to validate the approach, in terms of enhanced motion safety and shortened operational time. GRAPHICAL ABSTRACT: